Interações tróficas entre a espécie Geophagus brasiliensis e a comunidade de macroinvertebrados bentônicos em reservatórios de diferentes graus de trofia - Nunes, Marcos Vinicius (2012)
The studies related to the interactions among populations in the aquatic communities are essential for providing relevant information for the understanding of energy and matter pathways in the ecosystems and subsidize to the formulation of trophic web models.The occurrence of flexible diets is a marked feature of many species in the ichthyofauna of Tropical Rivers, where the same species can alternate the exploitation among food items according to the changes in the relative availability of food resources induced by temporal spatial and or ontogenetic changes. In this context, this study aimed to analyze the trophic interactions existing between the species Geophagus brasiliensis (Quoy & Gaimard, 1824) (Osteichthyes, Cichlidae), and benthic macroinvertebrate community in three reservoirs (Monjolinho Reservoir, Fazzari Reservoir, Broa Reservoir) in order to know its feeding mode, whether there is food selectivity or preference and which would be the most suitable trophic category for the species. Benthic macroinvertebrate communities in sediments sampled simultaneously to G. brasiliensis population were analysed and experiments were carried out in order to know the feeding mode of the species. Biometric measurements for ecomorphological analyses and analysis of stomach contents of the fishes were performed and based on qualitative and quantitative analyses of the macroinvertebrates consumed and their availability in the environment the values for the selectivity index of Paloheimo were calculated for the reservoirs sampled. The results showed that benthic macroinvertebrates are often used as food resource by the populations of G. brasiliensis with great participation in its diet, allowing us to characterize this species as a benthivore. Also, it was observed that G. brasiliensis has food preference for Chironomidae larvae.